Optimum Level of Organic and Inorganic Fertilizers Requirement for the Sustainable Productivity of Two Pipeline Clones of Potato - Khadka, YG; Khatri, BB; Raut, S; Chaudhari, D (Nepal Journal of Science and Technology, 2014)
The response of two pipeline potato clones to various levels of major nutrients (N: P2O5 and K2O) was studied during 2010/11 to 2011/12 at Hattiban Potato Research Farm, Khumaltar, Lalitpur. An experiment was laid out in a split plot design with three replications considering combinations of six different fertilizer levels as the main plot and three potato clones as sub-plot. The use of different doses of chemical fertilizers and 20 mt/ha farm yard manure (FYM) did not bring any improvements on soil properties. However, soil pH was slightly improved. The effect of different doses of chemical fertilizers was non-significant on plant emergence (at 30 DAP), ground cover and plant uniformity at 55 DAP. However, increased dose of N and K fertilizer gave taller plants and increased number of main stems per plant. Variety Kufri Jyoti performed better than both of the tested clones in the parameters such as plant emergence, ground cover and number of main stems per plant. Interaction effect was highly significant on number of stems per plant. Highest number of under and seed sized tubers were produced in the treatment with 100:100:60 N: P2O5: K2O kg/ha with 20 mt/ha, whereas highest number of over sized potato tubers were produced in the treatment 150:100:60 N: P2O5:K2O kg/ha and 20 mt/ha FYM. Total number of tubers and total weight (kg) was obtained highest in the treatment of 100:100:60 N: P2O5:K2O kg /ha with 20 mt/ha FYM. Variety Kufri Jyoti is still better yielding if there is no late blight disease in growing season. Though numbers of undersize and seed size tubers were produced highest from clone L 235-4, variety. Kufri Jyoti potato variety still is doing better in hill conditions of Nepal if the environment is not conducive to Phytophthora pathogens. Variety Kufri Jyoti has been able to produce highest yielded (30.9 t ha-1) in the application of 150:100:60 N: P2O5:K2O kg/ha and 200:100:60 N: P2O5:K2O kg/ha with 20 mt/ha FYM, whereas clone L 235-4 gave the highest yield (29.4 t ha-1) and clone CIP 389746.2 yielded highest (25.5 t ha-1). DOI: http://dx.doi.org/10.3126/njst.v14i2.10410 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 9-16